Microwave Dielectric Permittivity of Nanostructured RMn2O5 Manganate, R2Ti2O7 Titanate, and LiCoPO4 and LiNi0.5Co0.5PO4 Orthophosphate Composites - Anatoly B. Rinkevich; Dmitry V. Perov; Evgeny A. Kuznetsov; Maria S. Stenina (Nanomaterials, 2025)
The complex dielectric permittivity has been studied with the waves of millimeter wavelength for rare earth manganate and titanate and LiCoPO4 and LiNi0.5Co0.5PO4 orthophosphate composites. The measurements are carried out at frequencies of 26 to 38 GHz via measurements of transmission and reflection coefficients through a plate. A special method on how to extract the real and imaginary parts of dielectric permittivity is applied. Discussion is conducted on a nonmonotonic type of the frequency dependences for both real and imaginary parts of permittivity, and it has been shown that relaxation is non-Debye. The Cole–Cole, Havriliak–Negami, and Kohlrausch–Williams–Watts models cannot also explain the nonmonotonic frequency dependence of the real part of dielectric permittivity. Investigation of the structure and phase composition of nanocomposites has been carried out.